Membranes of Nata de coco-nanoparticles Fe3O4 For Diazinon Sensors - Didik Pramana; Ani Mulyasuryani; Rachmat Triandi Tjahjanto (The Journal of Pure and Applied Chemistry Research, 2018)
Development of diazinon sensors using mixed membranes of nata de coco and Fe3O4 nanoparticles on the SPCE (screen printed carbon electrode) surface has been carried out potentiometrically. The design of the sensor begins with the optimization of Fe3O4 nanoparticles added to the membranes of 50%, 67% and 75% while pH optimization using pH 4-5 acetate buffer and phosphate buffer pH 6-7. The diazinon sensor of the result has been tested at range concentration of 10-12 - 10-5mol.L-1. The results showed that the best sensor performance was 67% Fe3O4 nanoparticles and pH 5. The Nernst factor was 34.5 mV / decade, the detection limit value of 1,3 x 10-9mol.L-1 in the range concentration of 10-11 - 5x10-8 molL-1 with a response time of 140 seconds.